Joint inversion estimate of regional glacial isostatic adjustment in Antarctica considering a lateral varying Earth structure (ESA STSE Project REGINA). Issue 3 (29th August 2017) - Sasgen, Ingo; Martín-Español, Alba; Horvath, Alexander; Klemann, Volker; Petrie, Elizabeth J; Wouters, Bert; Horwath, Martin; Pail, Roland; Bamber, Jonathan L; Clarke, Peter J; Konrad, Hannes; Drinkwater, Mark R
Summary: A major uncertainty in determining the mass balance of the Antarctic ice sheet from measurements of satellite gravimetry, and to a lesser extent satellite altimetry, is the poorly known correction for the ongoing deformation of the solid Earth caused by glacial isostatic adjustment (GIA). Although much progress has been made in consistently modeling the ice-sheet evolution throughout the last glacial cycle, as well as the induced bedrock deformation caused by these load changes, forward models of GIA remain ambiguous due to the lack of observational constraints on the ice sheet's past extent and thickness and mantle rheology beneath the continent. As an alternative to forward-modeling GIA, we estimate GIA from multiple space-geodetic observations: Gravity Recovery and Climate Experiment (GRACE), Envisat/ICESat and Global Positioning System (GPS). Making use of the different sensitivities of the respective satellite observations to current and past surface-mass (ice mass) change and solid Earth processes, we estimate GIA based on viscoelastic response functions to disc load forcing. We calculate and distribute the viscoelastic response functions according to estimates of the variability of lithosphere thickness and mantle viscosity in Antarctica. We compare our GIA estimate with published GIA corrections and evaluate its impact in determining the ice-mass balance in Antarctica from GRACE and satellite altimetry. Particular focus is applied to the Amundsen Sea Sector in West Antarctica, where uplift rates of several centimetres per year have been measured by GPS. We show that most of this uplift is caused by the rapid viscoelastic response to recent ice-load changes, enabled by the presence of a low-viscosity upper mantle in West Antarctica. This paper presents the second and final contributions summarizing the work carried out within a European Space Agency funded study, REGINA (www.regina-science.eu ).